Detrimental impact on work productivity in patients with glaucoma: a systematic review - Hamza Inayat; Mura Abdul-Nabi; Bernice Leung; Jason Jiang; Sara Robertson; Monali S. Malvankar-Mehta (JFO Open Ophthalmology)
Introduction: Glaucoma, the leading cause of irreversible blindness globally, presents a growing public health concern with its prevalence expected to reach 111.8 million by 2040. This condition imposes both direct and indirect economic costs. In addition to medical expenses, indirect costs encompass lost productivity and adverse effects on mental health and independence. Early glaucoma stages primarily manifest as peripheral vision loss, but as it progresses, it significantly impairs one's quality of life. There is a growing body of research exploring the relationship between glaucoma and workplace functioning, including absenteeism and productivity loss. This systematic review aims to comprehensively investigate how glaucoma affects work productivity and the associated economic burden. Methods: This study adheres to the PRISMA guidelines. A literature search was conducted across multiple databases, including MEDLINE, Embase, CINAHL, and PsycINFO. Two independent reviewers screened titles, abstracts, and full-text articles based on predefined inclusion and exclusion criteria. Covidence software was employed for study selection and quality assessment. The Modified Downs and Black Checklist was used to evaluate study quality and thematic analysis was used to analyze data. Results: 17 studies met the inclusion criteria. The results revealed a significant impact of glaucoma on workplace functioning including, individuals with glaucoma experienced higher sickness absenteeism rates than those without glaucoma, glaucoma was associated with reduced labor force participation, leading to substantial productivity losses. Individuals with visual impairments and blindness earned less than those with normal vision, contributing to a significant financial burden. Glaucoma had a substantial impact on daily physical, emotional, and occupational functioning. Individuals with glaucoma faced limitations in performing daily activities and experienced difficulties in social interactions and household chores. Visual impairment due to glaucoma resulted in work disability, with some individuals reporting glaucoma-related visual disability as the main cause of their unemployment. A significant association between unemployment and glaucoma was observed in various studies, particularly in developing countries. Conclusion: Glaucoma significantly impairs work productivity and performance, resulting in substantial economic burdens on individuals, businesses, and society. Addressing these challenges requires multifaceted approaches, including workplace accommodations and holistic care.